Multinodular goitre surgery complications and directly observed surgeons’ skills: a prospective double-blind observational cohort study - Hafiz Naweed Ahmad; Fayyaz Ahmad; Admin (Journal of the Pakistan Medical Association, 2021)
Objective: To study multinodular goitre patients’ surgery by direct observation of surgical technique, and to compare complications with surgeons’ skills and experience, for improved training of future thyroid surgeons. Methods: Based on positivist epistemology and analytical observational design, this prospective double-blind study of a cohort of multinodular goitre patients operated upon by variedly experienced surgeons, was conducted at Bahawal Victoria Hospital Bahawalpur and Nishtar Medical University Hospital Multan, Pakistan, from December 2016 to April 2019. Patients were admitted through outpatient department and operated upon in routine operation lists. The surgeons were specialists/senior registrars, assistant professors, associate professors and professors. The patients were divided into two virtual groups: the one operated upon by surgeons with >3 years of post-fellowship experience and the other operated upon by surgeons with <3 years of post-fellowship experience. Surgeries were directly observed and differences in surgical technique and complications were recorded for respective groups. Data was analysed using SPSS 20. Results: Of the 134 patients, there were 73(54.5%) in group 1 and 61(45.5%) in group 2. Overall, there were 119(88.8%) females and 15(11.2%) males. The overall mean age was 37.17+/-13.41 years (range: 14-80 years). Of the 25 surgeons, 13(52%) were in group 1 and 12(48%) in group 2. Group 1 had fewer complications compared to group 2, which on certain parameters was statistically significant (p<0.05). Conclusion: Surgeons’ experience and technique were found to have significant relationship with the rate of complications. Direct observation of surgeries is significant for real life evaluation and training of junior surgeons.